Upper Limb Strikes Reactive Forces in Mix Martial Art Athletes during Ground and Pound Tactics - Beranek, Vaclav; Stastny, Petr; Novacek, Vit; Votapek, Petr; Formanek, Josef (International journal of environmental research and public health, 2020)
Athletes of mixed martial arts use a ground and pound strategy with the strikes in the dominant ground position. The aim of this study was to compare the average peak force (Fpeak) among three punches and to estimate the probability of achieving a skull bone fracture force of 5.1 kN for each type of strike in male and female athletes. A total of 60 males and 31 females (26 ± 8 years, 75 ± 20 kg, 177 ± 11 cm) practicing professional self-defense at the advanced and professional levels performed 15 strikes on a force plate. The analyses of 1360 trials showed significant differences among the strikes Fpeak in females (p < 0.01) and males (p < 0.01). Straight punches had lower Fpeak than palm strikes and elbow strikes in both genders, and palm strikes had higher Fpeak than elbow strikes in females. No difference was observed between palm strikes and elbow strikes in males (p = 0.09). The ground and pound strikes resulted in higher impacts than previously reported strikes in the standing position. Male athletes can deliver a Fpeak above 5.1 kN with a probability of 36% with elbow and palm strikes. Such forces can cause head injury; therefore, the use of these strikes in competition should be carefully considered.
Keywords: palm strike; Humans; loketní kloub; Martial Arts; bojové sporty; sportovci; Female; elbow strike; mixed martial arts; lidé; Elbow Joint; horní končetina; Athletes; ženské pohlaví; Male; Upper Extremity; straight punch; ground striking; head injuries; mužské pohlaví; system of self-defense